2014
DOI: 10.1136/annrheumdis-2014-205480
|View full text |Cite
|
Sign up to set email alerts
|

Alarmins S100A8/S100A9 aggravate osteophyte formation in experimental osteoarthritis and predict osteophyte progression in early human symptomatic osteoarthritis

Abstract: S100A8/A9 aggravate osteophyte formation in experimental OA with high synovial activation and may be used to predict osteophyte progression in early symptomatic human OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 33 publications
7
60
0
Order By: Relevance
“…Levels of S100A8/A9 in serum could be used as marker to assess synovial inflammation, as they have been described as inflammatory markers in various forms of arthritis such as rheumatoid arthritis, juvenile idiopathic arthritis and gout 19–21. Recently, we described the presence of S100A8/A9 in serum of patients with early symptomatic OA correlating with joint damage and osteophyte size 5 6. We now show that paquinimod is able to block production of proinflammatory and catabolic mediators induced by S100A9 in human OA synovium, in which CD68+ macrophages are present.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Levels of S100A8/A9 in serum could be used as marker to assess synovial inflammation, as they have been described as inflammatory markers in various forms of arthritis such as rheumatoid arthritis, juvenile idiopathic arthritis and gout 19–21. Recently, we described the presence of S100A8/A9 in serum of patients with early symptomatic OA correlating with joint damage and osteophyte size 5 6. We now show that paquinimod is able to block production of proinflammatory and catabolic mediators induced by S100A9 in human OA synovium, in which CD68+ macrophages are present.…”
Section: Discussionmentioning
confidence: 58%
“…Synovial activation is present in at least 50% of patients with OA2 and several proinflammatory mediators have been shown to be involved in OA pathology,3 4 among which alarmins S100A8 and S100A9. In recent studies, we showed that S100A8/A9 is high in serum and synovium of patients with OA and predictive for cartilage damage and osteophyte formation 5 6. We also found that paquinimod binds S100A9, but not S100A8, using photoaffinity labelling and surface plasmon resonance and specifically blocks the interaction of S100A9 7.…”
Section: Introductionmentioning
confidence: 61%
“…Human chondrocytes produce these molecules, and exposure of cartilage explants to S100A8 and S100A9 promoted catabolic (MMP-1, MMP-3, MMP-13, IL-6, IL-1β) and suppressed anabolic gene expression (aggrecan and Collagen type II) in a TLR-4 dependent manner [104]. Moreover, S100A9 deficient mice exhibited reduced disease in the collagenase model, but not the DMM model of OA, [104, 105] and disease was inhibited by pharmacologically reducing S100A9 expression [106]. The differential effects in these two models were attributed to more robust synovial activation in the collagenase model, which is induced by intra-articular injection of bacterial collagenase leading to instability of connective tissues.…”
Section: Methodsmentioning
confidence: 99%
“…Other timepoints, and pain-related outcomes particularly relevant to inflammation have not been examined. The data regarding S100 proteins [105] points to the importance of investigating multiple models, as the mechanism of disease induction may be an important variable impacting results. Therefore, whether observations from this study extend to other models and human PTOA has yet to be determined.…”
Section: Methodsmentioning
confidence: 99%
“…It is well established that several DAMPs are increased or decreased in various human diseases. Increased S100A8/A9 is associated with osteophyte progression in early human OA (89), suggesting that S100 proteins can be used as biomarkers for the diagnosis of the progressive grade of OA. Furthermore, many clinical studies have assessed the prognostic and predictive value of DAMPs, such as HSPs, ATP, and HMGB1, in cancer patients (90), which has raised the possibility that DAMPs may be useful prognostic factors for cancer.…”
Section: Damps As Biomarkers and Potential Therapeutic Targetsmentioning
confidence: 99%